Termo de referência para o gerenciamento de projetos integrados em uma instituição pública - Cintia Oliveira Campos (2010)
The present research contributes to project process in a hirer public financial institution. The participation of different agents in each project developed by the institution brings some problems that come from the lack of organization in the project process and in the information flow between its stakeholders such as: rework, delays in contracts deadlines and low quality of the final product. Due to the complexity of the project process, it has been searched in the process modeling a valid option tofulfill that blank. A Referential Term was developed by shaping the institutions project process through the systematization of solutions developed by other researchers. The present Term exposes theprocess, helps in its understanding and its practice, providing a general plan and establishing a detailed and integrated vision of the job made by every agent involved. The research was conducted by the implementation of this Term of reference in two project processes of the institution. It brings a discussion about the main aspects of the implementation and the main results, out of which, are highlighted an improve in the relations between the hirer and the hired, reduction of contracts deadlines,increase in information exchange, integration among designing teams, suppliers and other agents involved in the action.